Pengaruh Persepsi Keadilan Terhadap Kepuasan Pelanggan Pasca Pemulihan Layanan Pengguna Xl di Kota Denpasar - Rusadi, Febri; Santika, I Wayan (E-Jurnal Manajemen; Vol 3 No 9 (2014), 2014)
The purpose of this study was to determine the effect of distributive justice perceptions, perceptions of procedural justice, and interactional fairness perceptions on customer satisfaction after service recovery. Data was collected by way of interviews and distributed questionnaires to 80 respondents. Data were analyzed using multiple linear regression with SPSS software applications. The results showed: (1) Distributive justice perceptions positive and significant effect on customer satisfaction after service recovery. (2) The perception of procedural fairness positive and significant effect on customer satisfaction after service recovery. (3) Perceptions of interactional fairness positive and significant effect on customer satisfaction after service recovery. The implication of this research is the management of XL should be able to give a concrete manifestation of a debate result of adequate and acceptable to customers because of the perception of distributive justice had the greatest effect compared procedural and interactional justice on post- recovery customer satisfaction service.
Keywords: distributive justice, procedural justice, interactional justice, and customer satisfaction